T-Helper Cell Subset Response Is a Determining Factor in COVID-19 Progression - Gil-Etayo, Francisco Javier; Suàrez-Fernández, Patricia; Cabrera-Marante, Oscar; Arroyo, Daniel; Garcinuño, Sara; Naranjo, Laura; Pleguezuelo, Daniel E.; Allende, Luis M.; Mancebo, Esther; Lalueza, Antonio; Díaz-Simón, Raquel; Paz-Artal, Estela; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The immune response type organized against viral infection is determinant in the prognosis of some infections. This work has aimed to study Th polarization in acute COVID-19 and its possible association with the outcome through an observational prospective study. Forty-three COVID-19 patients were recruited in the Medicine Department of the hospital “12 de Octubre,” 40 patients remaining after losses to follow-up. Four groups were established according to maximum degree of disease progression. T-helper cells percentage and phenotype, analyzed by flow cytometer, and serum cytokines levels, analyzed by Luminex, were evaluated when the microbiological diagnosis (acute phase) of the disease was obtained. Our study found a significant reduction of %Th1 and %Th17 cells with higher activated %Th2 cells in the COVID-19 patients compared with reference population. A higher percent of senescent Th2 cells was found in the patients who died than in those who survived. Senescent Th2 cells percentage was an independent risk factor for death (OR: 31.11) accompanied by the numbers of total lymphocytes (OR: 0.05) with an AUC of 0.944. COVID-19 patients showed a pro-inflammatory serum cytokines profile when compared with controls, with higher levels of IL-2, IL-6, IL-10, IL-13, IL-15 and IP-10. Patients who did not survive presented significantly higher levels of IL-15 than those who recovered. No significant differences were observed according to disease progression groups. The study has shown that increased levels of IL-15 and a high Th2 response are associated with a fatal outcome of the disease.